2010
DOI: 10.1097/opx.0b013e3181ea1ad3
|View full text |Cite|
|
Sign up to set email alerts
|

Intra- and Intersession Repeatability of a Double-Pass Instrument

Abstract: Our findings showed that OQAS is a clinical instrument with a good intra- and intersession repeatability and that the realignment of the eye does not introduce any additional variability in the measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
3
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 25 publications
11
40
3
5
Order By: Relevance
“…It is known that the optical quality of the eye decreases with aging. 22,23 We know that these optical values in this study were lower than those in previous studies, 23,24 possibly because of the relatively high patient age. Until now, the postoperative visual performance after ICL implantation has been determined only in terms of visual acuity, higher order aberrations, or contrast sensitivity.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…It is known that the optical quality of the eye decreases with aging. 22,23 We know that these optical values in this study were lower than those in previous studies, 23,24 possibly because of the relatively high patient age. Until now, the postoperative visual performance after ICL implantation has been determined only in terms of visual acuity, higher order aberrations, or contrast sensitivity.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been demonstrated that the device has good repeatability, 23,24 and that the realignment of the eyes does not impose any additional variation on the measurements. 23 As shown in Figure 2, we confirmed the good repeatability of the measurements in the current study, as evidenced by the narrow 95% LoA.…”
Section: Discussionmentioning
confidence: 99%
“…Normal values for these parameters in a healthy young population, a post-refractive surgery group, and a cataract group have been reported. [47][48][49] The MTF cutoff corresponds to a 0.01 MTF value in the double-pass instrument because there is background noise in the MTF profile from the real recorded double-pass image. This parameter is directly related to the patient's visual acuity, although it is not affected by retinal and neural factors.…”
Section: Methodsmentioning
confidence: 99%
“…40,[47][48][49]55 From the image obtained by the double-pass system, the OSI is computed as the ratio between the amount of light recorded inside an annular area between 12 minutes of arc (arcmin) and 20 arcmin and that recorded closer to the peak, specifically in a circular area of a 1 arcmin radius from the central peak ( Figure 1). Although such aberrations and scattered light are distributed through the retinal image, 56,57 the OSI calculation is based on the concept that ocular aberrations mainly modify the intensity distribution closer to the peak and that the effect of ocular scattering occurs farther from the center.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 13 shows the double-pass images and the corresponding intensity profiles as a function of the angle (averaged section of the double-pass image), MTFs, and simulated vision using a standard visual acuity chart for an emmetropic eye, an eye with uncorrected astigmatism and an eye with spherical ametropia. The measurements were taken with the Optical Quality Analysis System (OQAS, Visiometrics, S.L., Spain) (Güell et al, 2006;Saad et al, 2010;Vilaseca et al, 2010a), which is a double-pass system currently available for use in daily clinical practice that includes this application. The double-pass technique has been used extensively to determine the optical quality of the eye, mainly by means of the ocular MTF.…”
Section: Clinical Assessment Of Retinal Image Quality In Eyes With Asmentioning
confidence: 99%